ANOSMIA AND COVID: A RELATIONSHIP STILL NOT CLARIFIED - Regina Portes Abrahão, Thayz; Aparecida Krichak, Bruna; Pires Bispo Andrade, Raquel; de Souza Gomes, Thaina; Gabriely da Silva Guedes, Shirley; Caroline Godoy, Luma; Begalli Vicentin, Isabelle; de Sousa Marques, Gabriela; Martins Duarte, Katiele; Michelli Luis Gimenez, Ana (Health and Society, 2025)
For a future doctor it is essential to know the pathophysiology of the diseases that affect their patients, so that they perform efficient care and if they do not find the cure leave the least possible damage with the best quality of life. Although anosmia is a mild symptom among patients affected by Covid 19, it brings consequences on the quality of life of the individual. Even being a pathology to be clarified in several points and despite being a symptom leads, it can lead to patient compromise in other areas, such as psychological. We must bear in mind that every human being is a bio-psycho-social being and although SARS-Cov-2 is a biological form it brings psychological damage to those infected. The factors that determined the choice of this topic are supported by the fact that they are the authors of the project, medical students where some of the colleagues were affected by covid-19 in more severe ways and even the mildest ones such as anosmia being a sequel after the convalescence period. It is intended to carry out exploratory research that involves a methodology with a bibliographic-documentary survey in a systematic way on the findings of causality between anosmia x Covid 19.